Towards a more inclusive library: Applying the four pillars of service inclusion in the Tolitoli regency library and archives service transformation - Nisa, Sakhratun; Yunus, Muhammad (Edelweiss Applied Science and Technology, 2025)
This research examines service inclusion in the transformation of the Tolitoli Regency Public Library in Indonesia through the lens of the Four Pillars of Service Inclusion: Enabling Opportunities, Offering Choice, Relieving Suffering, and Fostering Happiness. Employing a qualitative case study approach, data were collected through observations, in-depth interviews with 20 participants, and document analysis. The findings reveal the library’s commitment to creating an inclusive environment by providing equal access, embracing digital services, offering diverse facilities and programs, collaborating with communities, and addressing potential biases. However, challenges persist in enhancing access for vulnerable groups, maximizing the potential of digital services, expanding collaborations, improving infrastructure and comfort, and securing adequate funding. The study recommends providing specialized resources, engaging with disability organizations, investing in targeted outreach and digital infrastructure, expanding collaborations, improving facilities, developing staff training programs, refining satisfaction measurement systems, and advocating for funding by demonstrating the impact on community well-being. The research contributes to the understanding of service inclusion in public libraries and offers practical insights for library managers and policymakers in designing inclusive library services that promote social equity and empowerment.